Surprise Billing in Foot and Ankle Surgery and Its Effect on Patient Satisfaction - Joseph McCahon DO; Tara G. Moncman DO, MS; Tyler Radack BS; Mark Miller DO; Selene Parekh MD; David I. Pedowitz MD; Joseph Daniel DO (Foot & Ankle Orthopaedics, 2024)
Introduction/Purpose: Patients undergoing foot and ankle surgery may find themselves facing unexpected medical bills. This is known as surprise billing and has caused financial hardship for many patients, prompting policymakers to pass the “No Surprise Act”. The purpose of this study was to determine the incidence of surprise bills in patient undergoing foot and ankle surgery and the effect of surprise billing on patient satisfaction. Methods: This was a retrospective study of patients who underwent a foot and ankle surgery from May 2021 to November 2022 at a large multi-state institution. Patients completed a questionnaire regarding the incidence of surprise bills following their surgery, the details regarding those bills, and how those bills affected the surgical satisfaction. Results: Of the 771 responses, 23% of participants received at least one surprise bill following their foot and ankle procedure, with 39% of these bills being greater than $1000. The most common surprise bill came from the surgical facility (46%) followed by anesthesia (42%). Furthermore, the incidence of surprise billing before and after the implementation of the “No Surprise Act” on January 1st, 2022 was not found be significantly different (p=0.134). Patients who received surprise bills reported being significantly less satisfied with their surgery (p < 0.001) and felt their billing experience affected their surgical satisfaction. Conclusion: Despite recent legislative efforts, surprise billing in foot and ankle surgery is common and can negatively affect patient surgical satisfaction. Although surgeons may be unable to limit the amount of bills patients receive postoperatively, increased communication and education regarding the perioperative billing process may prove to be beneficial for both patient satisfaction and the doctor-patient relationship.